PENINGKATAN KEAKTIFAN BELAJAR MURID PADA PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN MENDALAM MENGGUNAKAN MEDIA KONKRET DAN MEDIA DIGITAL - Mega Susila Wati; Dhiny Rizkawati; syahrabanu, indik; Melly Agustin; Metha Oktapiani; Evie Luvita; Dyoty Auliya Vilda Ghasya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research was conducted to increase the learning engagement of fourth-grade elementary school students in mathematics lessons through a deep learning approach supported by concrete and digital media, prompted by the students’ low learning engagement, as indicated by an average engagement rate of 38% during the pre-cycle phase. The objective of this study was to increase student engagement through the implementation of deep learning stages supported by concrete and digital media. The method used was Classroom Action Research (CAR) based on the Kemmis and McTaggart model, implemented over three cycles. The research subjects consisted of 27 fourth-grade students at SD Negeri 39 Pontianak Kota during the 2025/2026 school year. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted by calculating the percentage of student learning engagement. The results showed an increase in student learning engagement in each cycle. The average level of learning engagement increased from 38% in the pre-cycle to 54% in Cycle I, 62% in Cycle II, and reached 81% in Cycle III. The highest indicator was the willingness to try practicing, with a percentage of 87% in Cycle III. These findings indicate that a deep learning approach supported by concrete and digital media can increase student learning engagement in mathematics instruction.